Relationship of Environmental Factors with Leptospirosis Incidence in Southeast Asia - Dwisiswanarum, Bella; Umniyati, Sitti Rahmah; Qaimumanazalla, Hayu; Wiratama, Bayu Satria; Ramadona, Aditya Lia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Southeast Asia is a leptospirosis endemic with the highest estimated incidence of cases. This type of research is a systematic review using the PRISMA. These search results found 2.322 research articles and only thirteen articles that matched the research criteria. Two articles discussed the relationship between sewer conditions and the incidence of leptospirosis, one article discussed the relationship between the presence of trash bins and the incidence of leptospirosis, nine articles discussed the presence of rats and the incidence of leptospirosis, and one article discussed standing water and the incidence of leptospirosis. There is a relationship between the presence of trash bins, the presence of rats, and standing water and the incidence of leptospirosis in Indonesia, Thailand, and Malaysia and there is no relationship between sewer conditions in Thailand and Indonesia.